2018
DOI: 10.1200/jco.2018.36.4_suppl.6
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted minimally invasive thoraco-laparoscopic esophagectomy versus open transthoracic esophagectomy for resectable esophageal cancer: A randomized controlled trial.

Abstract: 6 Background: The standard curative treatment for patients with esophageal cancer is perioperative chemotherapy or preoperative chemoradiotherapy followed by open transthoracic esophagectomy (OTE). Robot-assisted minimally invasive thoraco-laparoscopic esophagectomy (RAMIE) may reduce perioperative complications and improve functional recovery. Methods: In this randomized controlled trial, 112 patients with resectable intrathoracic esophageal cancer were randomly assigned to RAMIE or OTE. The composite primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…Other inclusion criteria were: oesophagectomy scheduled at least 2 weeks after the baseline measurement, a good understanding of the instructions of IMT and ability to perform the IMT programme. Exclusion criteria were: unable to communicate in the mother language spoken at the participating centre, age less than 18 years and participation in another trial with similar endpoints 20,21 .…”
Section: Methodsmentioning
confidence: 99%
“…Other inclusion criteria were: oesophagectomy scheduled at least 2 weeks after the baseline measurement, a good understanding of the instructions of IMT and ability to perform the IMT programme. Exclusion criteria were: unable to communicate in the mother language spoken at the participating centre, age less than 18 years and participation in another trial with similar endpoints 20,21 .…”
Section: Methodsmentioning
confidence: 99%
“…Since 2012, a prospective randomized clinical trial comparing robot-assisted minimally invasive thoracolaparoscopic esophagectomy versus open transthoracic esophagectomy for resectable esophageal cancer (RO-BOT trial) has been conducted in order to determine whether RE will reduce postoperative complications, blood loss, and hospital stay, being associated with at least similar oncological outcomes and better postoperative quality of life in comparison with open transthoracic esophagectomy. 72 Further studies are warranted to determine advantages and disadvantages of RE.…”
Section: Esophagectomy For Esophageal Cancermentioning
confidence: 99%
“…Therefore, robot-assisted three-stage esophagectomy is a safe and feasible technique for the treatment of esophageal cancer in selected patients. However, results of a randomized trial with long-term oncological outcomes (ROBOT trial) are awaited in this regard [10].…”
Section: Resultsmentioning
confidence: 99%
“…Noshiro et al [7] and Fabian et al [8] in their comparison of prone versus left lateral decubitus position during thoracoscopic esophageal mobilization found many advantages with prone position. In thoracic-phase port placement, Boone et al [9] and van der Sluis et al [10] have reported the use of two assistant ports in the left lateral decubitus position. We used one assistant port with ease in the prone position, as is reported by Kim et al [11].…”
Section: Discussionmentioning
confidence: 98%